Advertising dental services in dentistry - Zagrađanin Danica (Stomatološki glasnik Srbije, 2005)
Advertising in dentistry, as it is in medicine, takes more and more time in different kinds of media. Advertising without any control commercialises medical profession and it is harmful for the reputation of a doctor and the whole profession. The law that could strictly regulate the advertising has not yet been made, and more order should be made in this particular area. .